Weight reduction is associated with improvement of glycemic control in Japanese men, whose hemoglobin A1C is 5.6–6.4%, with visceral fat accumulation, but not without visceral fat accumulation. Issue 5 (22nd April 2013) - Okauchi, Yukiyoshi; Iwahashi, Hiromi; Okita, Kohei; Funahashi, Tohru; Kishida, Ken; Noguchi, Midori; Ohira, Tetsuya; Nakamura, Tadashi; Imagawa, Akihisa; Shimomura, Iichiro
Abstract Aims/Introduction The aim of the present study was to determine whether weight reduction is associated with improvement of glycemic control in non‐obese and obese subjects with or without visceral fat accumulation, whose hemoglobin A1c (A1C) is 5.6–6.4%. Materials and Methods A total of 798 male subjects whose A1C levels were between 5.6% and 6.4% were divided into subgroups based on body mass index (BMI) and/or estimated visceral fat area (eVFA), and were analyzed with respect to the relationships between 1‐year changes in BMI (ΔBMI) and A1C (ΔA1C). Results In both the BMI ≥25 and BMI <25 groups, ΔA1C correlated positively with ΔBMI (BMI ≥25 (n = 321): r = 0.236, P < 0.0001; BMI <25 (n = 477): r = 0.095, P = 0.0387) although the r‐value was very small for the latter group. In addition, for the group with eVFA ≥100 cm2 (n = 436), ΔA1C correlated positively with ΔeVFA (r = 0.150, P = 0.0017), but this correlation was not found for the eVFA <100 cm2 group (n = 339, P = 0.3505). Furthermore, ΔA1C positively correlated with ΔBMI for the groups in BMI ≥25 with eVFA >100 cm2 (n = 293, r = 0.256, P < 0.0001) and BMI <25 with eVFA ≥100 cm2 (n = 145, r = 0.250, P = 0.0024), but not for the groups in BMI ≥25 with eVFA <100 cm2 (n = 28, P = 0.6401) nor BMI <25 with eVFA <100 cm2 (n = 332, P = 0.6605). Conclusions These results suggest that the assessment of visceral fat, rather than BMI, might be more important in identifying subjects in whom lifestyle intervention aiming at weight reduction could be effective to prevent diabetes. This trial was registered with University Hospital Medical Information Network Clinical Trials Registry (no. UMIN 000002391).